Manejo da irrigação do feijoeiro cultivado em plantio direto no sistema integração lavoura-pecuária - CUNHA, Paulo César Ribeiro da (2009)
The water is becoming a resource more and more scarce, with growing strategic importance in the sections environmental, economical, social and political. The irrigated agriculture is responsible for considerable portion of the agricultural production, however, it is the activity that more it demands water. In the irrigated areas, one of the most important factors is the determination of the water levels for replacement of the losses happened in function of the evapotranspiration, with consequent it gets better of the productive efficiency. Inside of this context he becomes evident the need of administration of the applied water for the irrigation. The objective of this work was to evaluate the acting of three irrigation management methods in beans crop cultivated in direct planting in the system integration farming-cattle; the methods were appraised as for the estimate of the evapotranspiration, levels and irrigation frequency, productivity of grains and their components. It was also evaluated in the periods annual, dry and rainy season, the acting of methods of determination of the coefficient of the class A pan (Kp), and still, the possibility of adoption of a fixed value for such variable. The evaluation was made within the dear evapotranspiração with class A pan using the appraised coefficients and the dear for the standard method Penman-Monteith (FAO 56). The work was driven in the experimental area of Capivara farm, Rice and Beans Research Center in Santo Antônio de Goiás, Goiás State, Brazil. In the evaluation of the irrigation management methods the common bean crop was used (Phaseolus vulgaris L.) cv. BRS Supremo; the appraised methods were tensiometry, class A pan and Penman-Monteith. There were significant differences as for the productivity, number of grains for plant and height of plants in relation to the irrigation management methods, tends the class A pan propitiated the obtaining of larger yield, due to the largest total water, and of the largest irrigation frequencies, the management for tensiometry caused reduction of 40% in the total demand of water of the beans crop, however, with significant reductions in the productivity, tends the class A pan overestimated and of the underestimated tensiometry the total water esteemed by the standard method FAO 56 Penman-Monteith. Independent of Kp, the method of the class A pan overestimated the evapotranspiration obtained with Penman-Monteith. For the climatic conditions in which he took place the work, the best method of determination of Kp, for the estimate of ET0 in the annual period was it of Pereira et al. (1995). For the dry season it was it proposed by Cuenca (1989). In the rainy season all of the methods presented low actings, however, Pereira et al. (1995) method it was shown more efficient. It was observed that the method of the class A pan is not efficient to esteem ET0 in the rainy season. The analyses showed that the adoption of a fixed and constant Kp in 0,70 showed in high acting, mainly in the annual and dry seasons.